Zinc-doped calcium phosphate porous ceramic scaffold as well as preparation method and application thereof

By preparing zinc-doped calcium phosphate porous ceramic scaffolds, the problems of high infection risk and insufficient osteogenic activity of β-TCP materials in bone defect repair were solved, and a scaffold with high biocompatibility and excellent mechanical properties was achieved, which is suitable for bone defect repair.

CN120661746APending Publication Date: 2025-09-19SOUTHWEST JIAOTONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510935383.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

Existing β-TCP materials have problems such as high infection risk and insufficient osteogenic activity in bone defect repair, which limits their widespread application in clinical practice.

Method used

By adopting the preparation method of zinc-doped calcium phosphate porous ceramic scaffold, a β-TCP scaffold with a regular pore structure and uniform zinc doping was prepared through light-curing 3D printing technology combined with hydrothermal method and high-throughput technology, optimizing its biocompatibility and mechanical properties.

Benefits of technology

The osteogenic activity and biocompatibility of the β-TCP scaffold were improved, and its mechanical properties were enhanced. In particular, 10% Zn-β-TCPS showed the best mechanical properties, with a compressive strength of 0.55 MPa, achieving an ideal mechanical support effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120661746A_ABST
    Figure CN120661746A_ABST
Patent Text Reader

Abstract

The invention provides a zinc-doped calcium phosphate porous ceramic scaffold as well as a preparation method and application thereof, and belongs to the technical field of medical materials. The preparation method comprises the following steps: dissolving a calcium source and a zinc source in water to obtain a calcium-zinc mixed solution; dropwise adding the phosphorus source solution into the calcium-zinc mixed solution, and adding ammonia water to adjust the pH value of the system to obtain a suspension; performing hydrothermal reaction on the suspension to obtain zinc-doped calcium phosphate slurry; and with polyvinyl alcohol as a binder, blade-coating the zinc-doped calcium phosphate slurry on a printing platform, and carrying out photocuring 3D printing to obtain the zinc-doped calcium phosphate porous ceramic scaffold. Researches show that all scaffolds take beta-TCP as a main phase, and zinc doping does not change a beta-TCP characteristic functional group structure; a static mechanical experiment shows that the 10% Zn-beta-TCPS shows the most excellent mechanical property, and the compressive strength reaches 0.55 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical materials, and in particular to a zinc-doped calcium phosphate porous ceramic stent and a preparation method and application thereof. Background Art

[0002] Bone defects are a common problem in orthopedic clinics, primarily caused by factors such as fracture trauma, osteomyelitis, and tumors. Currently, treatments for bone defects primarily include autologous bone transplantation, allogeneic bone transplantation, and synthetic bone graft transplantation. However, autologous and allogeneic bone transplantation face numerous limitations in clinical application, such as limited donor sites, high costs, difficulty in tissue acquisition, and potential risks of infectious diseases. Therefore, the development of safe, effective, and economical bone repair materials has become a current research priority.

[0003] Synthetic bone substitutes have attracted widespread attention due to their advantages, including lack of immune rejection, no risk of disease transmission, and excellent osteoconductivity. β-tricalcium phosphate (β-TCP) has become one of the most commonly used and effective synthetic bone graft substitutes due to its excellent biocompatibility, osteoconductivity, and chemical composition similar to natural bone. However, traditional β-TCP materials have two major limitations in clinical application: first, the high risk of infection after implantation, which affects the therapeutic effect; second, the osteogenic activity needs to be further improved, especially in the repair of complex bone defects. These issues have restricted the widespread application of β-TCP materials in clinical practice.

[0004] Therefore, how to obtain a β-TCP material with high osteogenic activity and good biocompatibility is a technical problem that needs to be solved at present. Summary of the Invention

[0005] The purpose of the present invention is to provide a zinc-doped calcium phosphate porous ceramic scaffold and its preparation method and application, so as to solve the above technical problems.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a zinc-doped calcium phosphate porous ceramic scaffold, comprising the following steps:

[0008] 1) dissolving a calcium source and a zinc source in water to obtain a calcium-zinc mixed solution;

[0009] 2) adding the phosphorus source solution dropwise to the calcium-zinc mixture, and adding ammonia water to adjust the pH of the system to obtain a suspension;

[0010] 3) subjecting the suspension to a hydrothermal reaction to obtain a zinc-doped calcium phosphate slurry;

[0011] 4) Using polyvinyl alcohol as a binder, the zinc-doped calcium phosphate slurry was scraped onto the printing platform, and a zinc-doped calcium phosphate porous ceramic scaffold was obtained by light-curing 3D printing.

[0012] Furthermore, the calcium source comprises calcium nitrate and / or calcium chloride; the zinc source comprises zinc nitrate and / or calcium zinc chloride; the molar ratio of the calcium source to the zinc source is 8-9.5:0.5-2; the calcium zinc mixed solution contains calcium nitrate and / or calcium zinc chloride; the molar ratio of the calcium source to the zinc source is 8-9.5:0.5-2; 2+ +Zn 2+ The molar concentration is 1 mol / L.

[0013] Furthermore, the molar ratio of the phosphorus source to the zinc source is 0.5-2:5-7.

[0014] Furthermore, the ammonia water is used to adjust the pH of the system to 7-10.

[0015] Furthermore, the temperature of the hydrothermal reaction is 100-200° C., and the time of the hydrothermal reaction is 5-15 hours.

[0016] Furthermore, the zinc-doped calcium phosphate slurry is applied to a thickness of 150 to 200 μm.

[0017] The present invention also provides a zinc-doped calcium phosphate porous ceramic bracket prepared by the above preparation method.

[0018] The present invention provides an application of a zinc-doped calcium phosphate porous ceramic scaffold in repairing bone defects.

[0019] Beneficial effects of the present invention:

[0020] The present invention uses light-curing 3D printing technology to prepare β-TCP scaffolds with different zinc doping rates. SEM observations show that the zinc-doped β-TCPS has a highly regular pore structure, and EDS elemental analysis confirms the successful doping of zinc. XRD and FTIR analysis results show that all scaffolds are mainly composed of β-TCP, and zinc doping does not change the characteristic functional group structure of β-TCP. Static mechanical experiments show that 10% Zn-β-TCPS exhibits the best mechanical properties, with a compressive strength of 0.55 MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The SEM images of β-TCP powders with different zinc doping rates of the present invention are shown below;

[0022] Figure 2 Sintering curves of β-TCP scaffolds with different zinc doping rates prepared in the embodiments of the present invention;

[0023] Figure 3 Optical images of β-TCP scaffolds with different zinc doping rates before and after sintering;

[0024] Figure 4 The SEM images of β-TCP scaffolds with different zinc doping rates of the present invention are shown;

[0025] Figure 5 This is the EDS analysis diagram of 10% Zn-β-TCPS;

[0026] Figure 6 Characterization diagrams of β-TCP scaffolds with different zinc doping rates of the present invention, Figure A shows the scaffold porosity, and Figure B shows the scaffold pore size distribution;

[0027] Figure 7 The XRD diffraction patterns of β-TCP scaffolds with different zinc doping rates of the present invention are shown in FIG.

[0028] Figure 8 FTIR spectra of β-TCP scaffolds with different zinc doping rates of the present invention;

[0029] Figure 9 Figure 1 is a characterization diagram of the mechanical properties of the β-TCP scaffold with different zinc doping rates of the present invention, where A is the compressive strength and B is the stress-strain curve. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing a zinc-doped calcium phosphate porous ceramic scaffold, comprising the following steps:

[0031] 1) dissolving a calcium source and a zinc source in water to obtain a calcium-zinc mixed solution;

[0032] 2) adding the phosphorus source solution dropwise to the calcium-zinc mixture, and adding ammonia water to adjust the pH of the system to obtain a suspension;

[0033] 3) subjecting the suspension to a hydrothermal reaction to obtain a zinc-doped calcium phosphate slurry;

[0034] 4) Using polyvinyl alcohol as a binder, the zinc-doped calcium phosphate slurry was scraped onto the printing platform, and a zinc-doped calcium phosphate porous ceramic scaffold was obtained by light-curing 3D printing.

[0035] In the present invention, the calcium source comprises calcium nitrate and / or calcium chloride, preferably calcium nitrate; the zinc source comprises zinc nitrate and / or zinc chloride, preferably zinc nitrate; the molar ratio of the calcium source to the zinc source is 8 to 9.5:0.5 to 2, preferably 9.5:0.5, 9:1, 8:2; the calcium zinc mixed solution contains calcium nitrate and / or calcium chloride, preferably calcium nitrate; the molar ratio of the calcium source to the zinc source is 8 to 9.5:0.5 to 2, preferably 9.5:0.5, 9:1, 8:2; the calcium zinc mixed solution contains calcium nitrate and / or zinc chloride, preferably zinc ... 2+ +Zn 2+ The molar concentration is 1 mol / L.

[0036] In the present invention, the molar ratio of the phosphorus source to the zinc source is 0.5-2:5-7, preferably 0.5-2:6.

[0037] In the present invention, the ammonia water is used to adjust the pH of the system to 7-10, preferably pH=8.

[0038] In the present invention, the temperature of the hydrothermal reaction is 100-200° C., preferably 120-180° C., and more preferably 150° C.; the time of the hydrothermal reaction is 5-15 h, preferably 8-12 h.

[0039] In the present invention, the thickness of the zinc-doped calcium phosphate slurry applied by scraping is 150-200 μm, preferably 175 μm.

[0040] The present invention also provides a zinc-doped calcium phosphate porous ceramic bracket prepared by the above preparation method.

[0041] The present invention provides an application of a zinc-doped calcium phosphate porous ceramic scaffold in repairing bone defects.

[0042] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0043] Example 1

[0044] Ca(NO3)2·4H2O and Zn(NO3)2·6H2O were magnetically stirred until they were completely dissolved. 2+ +Zn 2+ ) concentration is 1M, Zn 2+ and Ca 2+ The molar ratio of (NH4)2HPO4 is 0.5:9.5. Add (NH4)2HPO4 into deionized water and stir magnetically until it is completely dissolved. 3- The concentration is 0.6 M. 50 mL of (NH4)2HPO4 solution is added dropwise to a mixed solution of equal volumes of Ca(NO3)2·4H2O and Zn(NO3)2·6H2O using a pipette. 2+ +Zn 2+ ) / PO4 3- =5 / 3. After the dropwise addition, stir for 5 minutes, then add 1.0 mL of aqueous ammonia to adjust the pH to 8, and continue stirring for 25 minutes. Transfer the suspension to a reactor and set the reaction temperature at 150°C for 8 hours. The resulting sample is labeled 5% Zn-β-TCP.

[0045] Example 2

[0046] Same as Example 1, except that Zn 2+ and Ca 2+ The molar ratio of Zn-β-TCP is 1:9, and the sample is labeled as 10% Zn-β-TCP.

[0047] Example 3

[0048] Same as Example 1, except that Zn 2+ and Ca 2+The molar ratio of Zn-β-TCP is 2:8, and the sample is labeled as 20% Zn-β-TCP.

[0049] Example 4

[0050] The 3D model was created and sliced ​​using Materialise Magics and 10dim slicing software, respectively. Each layer was 50 μm thick, and the sliced ​​files were imported into a digital light processing (DLP) device. Using polyvinyl alcohol (PVA) as a binder, the prepared β-TCP, 5% Zn-β-TCP, 10% Zn-β-TCP, and 20% Zn-β-TCP slurries were poured into the DLP device's squeegee slot. The blade level and height were adjusted, and the slurry was then applied to a thickness of approximately 175 μm. After adjusting printing parameters such as squeegee speed, exposure time for the first layer, exposure time for the remaining layers, and exposure power for the remaining layers, click "Start" to automatically print. After printing, the β-TCP scaffold (β-TCPS), 5% Zn-β-TCP scaffold (5% Zn-β-TCPS), 10% Zn-β-TCP scaffold (10% Zn-β-TCPS), and 20% Zn-β-TCP scaffold (20% Zn-β-TCPS) were gently scraped onto the build table using a spatula. The scaffolds were then placed in an ultrasonic cleaner containing a detergent to remove any residual slurry from the surface. The cleaned scaffolds were then sintered after standing at room temperature for 72 hours. The sintered scaffolds were then sealed and stored for future use.

[0051] The present invention combines high-throughput technology with a hydrothermal method for the synthesis of calcium phosphate and the screening of process parameters. It is found that as the introduction of zinc ions increases, the morphology of calcium phosphate gradually changes from rod-like particles to a cluster structure composed of rod-like particles. The rod-like particles on the cluster structure gradually fuse to form a complete crystal face, and the crystal face gradually develops into a complete block-like particle (see Appendix Figure 1 ).

[0052] The synthesized 5%, 10% and 20% zinc-doped calcium phosphate were prepared into porous scaffolds by 3D printing technology. The prepared porous scaffolds were sintered at high temperature. The sintering curves are shown in Fig. Figure 2 shown.

[0053] The scaffolds prepared by 3D printing all showed a uniform yellow color before sintering (such as Figure 3 ), which is due to the organic binder added during the printing process. After high-temperature sintering, the organic components are removed from the scaffold, resulting in a pure white color. The overall shape and size of the scaffold remain stable before and after sintering, with no significant deformation or shrinkage, indicating that the sintering process parameters were set appropriately. Notably, the scaffold retains its intact three-dimensional porous structure after sintering, with interconnected pores, which facilitates nutrient transport and cell growth.

[0054] SEM images show ( Figure 4), it can be clearly seen that the 3D printed scaffold has a highly regular pore structure, which is conducive to cell migration and angiogenesis, and can also provide an ideal microenvironment for bone tissue regeneration. To further characterize the elemental composition and distribution of the scaffold, EDS analysis was performed on 10% Zn-β-TCPS. Figure 5 As shown in the figure, the four elements Ca, Zn, P, and O are evenly distributed on the scaffold surface, without obvious element segregation. The uniform distribution of Zn element confirms the successful doping of zinc ions into the β-TCP lattice.

[0055] Figure 6 The results show that the porosity of each scaffold group exceeded 80%, with a pore size between 450-500 μm. Studies have shown that scaffolds with a pore size greater than 300 μm are beneficial for capillary growth and new bone formation.

[0056] like Figure 7 XRD results showed that all four scaffolds were primarily composed of β-TCP and contained a small amount of calcium pyrophosphate. The 10% Zn-β-TCPS and 20% Zn-β-TCPS also contained a small amount of zinc pyrophosphate, with the 20% Zn-β-TCPS containing a higher zinc pyrophosphate content than the 10% Zn-β-TCPS. Studies have confirmed that both calcium pyrophosphate and zinc pyrophosphate have good biocompatibility.

[0057] Figure 8 The FTIR results show that the functional group positions of the characteristic peaks of Zn-β-TCPS and the main phase β-TCP are consistent, such as Figure 8 As shown. 1380cm -1 The wave number at 1650 cm corresponds to the in-plane bending of POH, -1 The broad band above 650 cm is related to the HOH bending and the rotation of the remaining free water. -1 The wave number at corresponds to the absorption peak of crystalline water of pyroxenite

[142] , 727cm -1 It is the absorption peak of pyrophosphate. -1 、605cm -1 , 941cm -1 and 1120cm -1 The broadband at PO4 3- The stretching vibration peak is shown in the gray area in the figure.

[0058] The mechanical properties test results of the stent showed that the introduction of zinc ions significantly improved the mechanical properties of the stent. Figure 9As shown, with increasing zinc doping levels, the compressive strength of the scaffolds initially increases and then decreases. All Zn-β-TCPS samples exhibited compressive strengths exceeding 0.5 MPa, meeting the strength requirements for load-bearing bone repair scaffolds. Among them, 10% Zn-β-TCPS exhibited the most excellent mechanical properties, reaching a compressive strength of 0.55 MPa, a 45% increase compared to undoped β-TCPS. This is attributed to the most uniform grain size distribution in 10% Zn-β-TCPS, consistent with the SEM results. These results demonstrate that a 10% zinc doping level achieves the optimal balance in optimizing scaffold mechanical properties, providing ideal mechanical support for bone defect repair.

[0059] As can be seen from the above examples, the present invention provides a zinc-doped calcium phosphate porous ceramic scaffold, its preparation method, and application. Using photocurable 3D printing technology, the present invention prepared β-TCP scaffolds with varying zinc doping ratios. Scanning electron microscopy (SEM) observations of the zinc-doped β-TCPS revealed a highly regular pore structure, and EDS elemental analysis confirmed the successful zinc doping. XRD and FTIR analysis results showed that all scaffolds were primarily composed of β-TCP, and zinc doping did not alter the characteristic functional group structure of β-TCP. Static mechanical tests revealed that 10% Zn-β-TCPS exhibited the best mechanical properties, with a compressive strength of 0.55 MPa.

[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a zinc-doped calcium phosphate porous ceramic scaffold, characterized in that: The following steps are involved: 1) dissolving a calcium source and a zinc source in water to obtain a calcium-zinc mixed solution; 2) adding the phosphorus source solution dropwise to the calcium-zinc mixture, and adding ammonia water to adjust the pH of the system to obtain a suspension; 3) subjecting the suspension to a hydrothermal reaction to obtain a zinc-doped calcium phosphate slurry; 4) Using polyvinyl alcohol as a binder, the zinc-doped calcium phosphate slurry was scraped onto the printing platform, and a zinc-doped calcium phosphate porous ceramic scaffold was obtained by light-curing 3D printing.

2. The method for preparing the zinc-doped calcium phosphate porous ceramic scaffold according to claim 1, wherein: The calcium source comprises calcium nitrate and / or calcium chloride; the zinc source comprises zinc nitrate and / or zinc chloride; the molar ratio of the calcium source to the zinc source is 8-9.5:0.5-2; the calcium zinc mixed solution contains calcium nitrate and / or calcium ... 2+ +Zn 2+ The molar concentration is 1 mol / L.

3. The method for preparing the zinc-doped calcium phosphate porous ceramic scaffold according to claim 1 or 2, characterized in that: The molar ratio of the phosphorus source to the zinc source is 0.5-2:5-7.

4. The method for preparing the zinc-doped calcium phosphate porous ceramic scaffold according to claim 3, wherein: The ammonia water is used to adjust the pH of the system to 7-10.

5. The method for preparing the zinc-doped calcium phosphate porous ceramic scaffold according to claim 1, 2 or 4, wherein: The temperature of the hydrothermal reaction is 100-200° C., and the time of the hydrothermal reaction is 5-15 hours.

6. The method for preparing the zinc-doped calcium phosphate porous ceramic scaffold according to claim 5, characterized in that: The thickness of the zinc-doped calcium phosphate slurry applied by scraping is 150-200 μm.

7. The zinc-doped calcium phosphate porous ceramic scaffold prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the zinc-doped calcium phosphate porous ceramic scaffold according to claim 7 in repairing bone defects.